2019
DOI: 10.1002/jcb.29501
|View full text |Cite
|
Sign up to set email alerts
|

Impact of modulation of telomerase and cancer stem‐cell marker OCT4 axis in cervical cancer pathogenesis with underlying HPV16 infection

Abstract: Lacunae exist in the molecular event(s) specificity associated with cervical cancer (CaCx) pathogenesis. The present study aimed to evaluate the significance of telomerase‐cervical cancer stem cells (CSCs) modulation in CaCx pathogenesis with underlying HPV16 infection. The study included HPV16 positive cases only (N = 65) of the total enrolled cases from Northeast India. The analysis of viral load and the differential messenger RNA expression of E6, E7, hTERT, hTR, and cancer stem‐cell markers was studied by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Tyagi et al (43) clarified the role of the HPV E6 oncogene in the maintenance of the stemness characteristics (stemness markers OCT4, SOX2, Nanog, Lrig1, and CD133) of CSCs in CC. Significant OCT4 marker upregulation has also been found in CC, which has an association with disease susceptibility and severity (44). Other research has indicated that ALDH1 and POU class 5 homeobox 1 (OCT4) may be utilized as biomarkers for the early detection of CC or monitoring the treatment of patients (45).…”
Section: Discussionmentioning
confidence: 99%
“…Tyagi et al (43) clarified the role of the HPV E6 oncogene in the maintenance of the stemness characteristics (stemness markers OCT4, SOX2, Nanog, Lrig1, and CD133) of CSCs in CC. Significant OCT4 marker upregulation has also been found in CC, which has an association with disease susceptibility and severity (44). Other research has indicated that ALDH1 and POU class 5 homeobox 1 (OCT4) may be utilized as biomarkers for the early detection of CC or monitoring the treatment of patients (45).…”
Section: Discussionmentioning
confidence: 99%
“…However, different studies indicated that OCT4 expression in tumor tissues is enhanced in different cancers . 9,30 In the study conducted by Talebi et al, OCT4 expression was analyzed in normal and colon adenocarcinoma tissues. Their results showed no statistically significant association between OCT4 expression and cancer incidence .…”
Section: Association Between Oct4 Expression Nanog Expression and The Patients' Clinical And Pathological Characteristicsmentioning
confidence: 99%
“…For instance, OCT4 collaborated with NCOR1 precipitated transcriptional repression on high expression genes in MEFs ( 22 ). Additionally, previous studies suggested that HPV16 E6 upregulated OCT4 expression by targeting HDAC1 for proteasomal degradation ( 17 , 28 b). Moreover, JNK-phosphorylated OCT4 reduced OCT4 protein stability which was enhanced by KAP1 overexpression ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 94%
“…The transcription factor OCT4 takes a crucial role in maintaining self-renewal and pluripotency of embryonic stem cells ( 16 ). The OCT4 was related to cervical cancer susceptiveness, which colocalized in the nucleus with HPV16 E6, suggesting the potential role of viral HPV16 E6 in stem-like cancer cells through regulating OCT4 expression ( 17 a). However, whether HPV16 E6-induced OCT4 expression could influence the level of p53 is still unknown.…”
Section: Introductionmentioning
confidence: 99%